1997
DOI: 10.1016/s0959-8049(96)00457-1
|View full text |Cite
|
Sign up to set email alerts
|

Benign and malignant thyroid lesions show instability at microsatellite loci

Abstract: Forty-six benign and m alignant tum ours and tu m ou r-lik e lesions o f the thyroid were analysed for m icrosatellite instability (MI) at eight loci, m ap p in g to four different ch rom osom es, 7 lesio n s (15%) displayed MI at one or more loci, in clu d in g 2/13 nodular goitres, 2/15 follicular ad en om as, 2/12 papillary carcinom as and 1/4 follicular carcin o m as. Two benign and one m alignant lesio n am ong the seven unstable cases exhibited this p h en otyp e at three or m ore loci. We found no m u t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…Higher incidence of MSI was observed using different panel of markers in malignant vs benign tumors (Stoler et al, 2002). Our present data is in concordance with the previous study using a different subset of markers (Soares et al, 1997). Another study described overall frequency of 21.5% in fifty-one thyroid tumors (Lazzereschi et al, 1999), which differs from ours.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Higher incidence of MSI was observed using different panel of markers in malignant vs benign tumors (Stoler et al, 2002). Our present data is in concordance with the previous study using a different subset of markers (Soares et al, 1997). Another study described overall frequency of 21.5% in fifty-one thyroid tumors (Lazzereschi et al, 1999), which differs from ours.…”
Section: Discussionsupporting
confidence: 91%
“…A study based on small series of cases and limited number of microsatellite markers examined could not show any evidence of MSI (Farid et al, 1994;Alves et al, 2000) whereas other reports have been suggestive of limited role of MSI in both benign and malignant tumors using the different set of microsatellite markers (Soares et al, 1997;Zhou et al, 1997;Tomita et al, 1999). In our present study, 66.6% of thyroid tumors exhibited MSI/LOH on examining six mono and four dinucleotide microsatellite markers, including all the benign tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The small series of nine cases reported by Vermiglio et al (1995) did not exhibit any MI, although a limited incidence of MI was observed in the larger series of tumours and tumour-like lesions analysed by Soares et al (1997). To explore the role of MI in thyroid carcinogenesis, we analysed the status of ten dinucleotide repeat microsatellite loci in a panel of 51 tumours and tumour-like lesions.…”
mentioning
confidence: 98%
“…2 Thus, transfection of mutant HRAS V12 or mutant BRAF V600E induced GIN in a rat thyroid cell line, manifesting as loss of chromosomal material, mitotic bridge formation and misaligned chromosomes. [3][4][5] Recently, we found RET oncogene amplification in human thyroid cancers. 6 Oncogene amplification is common in solid tumors and correlates with a poor prognosis for patients with ovarian cancer (HER-2/neu), breast cancer (C-MYC, HER-2/neu), neuroblastoma (N-MYC), or small cell lung cancer (C-MYC).…”
mentioning
confidence: 99%